Hepatic arterial infusion chemotherapy versus systemic therapy for advanced hepatocellular carcinoma: a systematic review and meta-analysis - Kim, Hyeon-Jong; Lee, Seung Hyuk; Shim, Hyun Jeong; Bang, Hyun Jin; Cho, Sang Hee; Chung, Ik-Joo; Hwang, Eu Chang; Hwang, Jun Eul; Bae, Woo Kyun (Frontiers in Oncology, 2023)
To investigate the effects of hepatic arterial infusion chemotherapy (HAIC) with or without systemic chemotherapy compared to systemic chemotherapy alone in patients with locally advanced hepatocellular carcinoma (HCC). Following a registered protocol (CRD42023386780), a comprehensive search was performed using reputable databases and registries up to December 26, 2022, with no language, publication date, or status restrictions. Only randomized controlled trials (RCTs) investigating the effects of HAIC with or without systemic chemotherapy versus systemic therapy alone were included. The primary outcomes were overall survival (OS), progression-free survival (PFS), and adverse events. The secondary outcomes included the objective response rate (ORR) and disease control rate (DCR). A random-effects model was used, and the certainty of the evidence was rated using GRADE.Seven RCTs involving 1,010 patients were included. All trials utilized sorafenib as the comparator. Five trials (690 patients) compared HAIC plus sorafenib to sorafenib alone, while two trials (320 patients) compared HAIC to sorafenib. The results indicate that HAIC, with or without sorafenib, may increase OS, PFS, and ORR compared with sorafenib alone. HAIC may enhance DCR, but the evidence is very uncertain. Adverse events were comparable between HAIC plus sorafenib and sorafenib alone. However, adverse events might be decreased in HAIC alone. HAIC with or without systemic chemotherapy may improve survival outcomes and response rates of patients with HCC. Since the current body of evidence is moderate to very low, more robust randomized trials are needed to confirm the efficacy of HAIC.